Théologie et ecclésiologie chez William Laud (1573-1645), archevêque de Cantorbéry - Pierre Lurbe (Revue LISA)
This article argues that William Laud’s theology and ecclesiology are strongly interrelated. A theologian who gave pride of place to sacramental life, and whose forceful rejection of predestination made him close to Arminianism, Laud followed in the footsteps of Saint Cyprian in upholding episcopacy as the proper form of government for the Church.